Dendritic Cells Enhance Growth and Differentiation of CD40-activated B Lymphocytes - Dubois, Bertrand (The Rockefeller University Press, 1997)
After antigen capture, dendritic cells (DC) migrate into T cell–rich areas of secondary lymphoid organs, where they induce T cell activation, that subsequently drives B cell activation. Here, we investigate whether DC, generated in vitro, can directly modulate B cell responses, using CD40L-transfected L cells as surrogate activated T cells. DC, through the production of soluble mediators, stimulated by 3- to 6-fold the proliferation and subsequent recovery of B cells. Furthermore, after CD40 ligation, DC enhanced by 30–300-fold the secretion of IgG and IgA by sIgD(−) B cells (essentially memory B cells). In the presence of DC, naive sIgD(+) B cells produced, in response to interleukin-2, large amounts of IgM. Thus, in addition to activating naive T cells in the extrafollicular areas of secondary lymphoid organs, DC may directly modulate B cell growth and differentiation.